Innovation in responsible management education : preparing the changemakers of tomorrow - Obexer, Regina; Wieser, Desiree; Baumgartner, Christian; Fröhlich, Elisabeth; Rosenbloom, Alfred; Zehrer, Anita (Emerald Publishing Limited, 2024)
The transformation of higher education required to prepare learners to tackle the pressing challenges of the 21st century and accelerate the UN Sustainable Development Goals (SDGs) remains fragmented and illusive. This is particularly problematic in the field of management education, where learners represent business leaders, managers and decision makers of the future. What is required is no less than a paradigm shift, where creative and innovative approaches to curriculum design and teaching and learning methods are implemented within a learning environment that recognizes and addresses real world challenges and contextual awareness. Featuring contributions from around the globe, Innovation in Responsible Management Education paints a rich picture of the diverse ways the challenges responsible leadership education is facing are being approached and responded to by recognized expert authors in the field. The chapters emphasize different thematic foci, including sustainable entrepreneurship, future studies, poverty alleviation, new capitalism, gamification, climate change, responsible leadership, change agents, effectiveness and quality measurement of programs.